Hyponatraemia: Pathophysiology, treatment and future directions - Liddy, Anne Marie (Trinity Student Medical Journal, 2010)
Hyponatraemia is the most common electrolyte abnormality in clinical practice. While it may be an incidental discovery or manifest with subtle symptoms such as mild confusion, it can also be associated with severe neurological complications and may even result in death. Mismanagement of hyponatraemia with over-rapid correction of the electrolyte abnormality can cause serious and long-lasting neurological consequences. An understanding of the pathophysiology of hyponatraemia is necessary in order to select the appropriate treatment and avoid the complications associated with this condition and its management. The recent introduction of vasopressin receptor antagonists offers clinicians a new option in the management of this challenging condition.